(untitled) (Research, Society and Development, 2025)
Kefir is a fermented dairy product rich in micronutrients that contribute to human health and well-being. Sucrose is the most used sweetener added, however, if consumed in excess can cause harm to health beyond. An alternative to sucrose is fruit pulp, such as jabuticaba, which contains natural sugars, great nutritional value and can improve flavor to the final product. This present study aimed to evaluate the effect of different concentrations of sucrose and prebiotic jabuticaba pulp in milk kefir, evaluating the physicochemical, microbiological and sensory properties for 30 days of storage. The kefir fermentation process was characterized analyzing pH, acidity, total soluble solids (TSS) content, and count of yeasts and lactic acid bacteria (LAB). Afterwards, 5 kefir formulations were prepared, with 5% and 7.5% of sucrose, 5% and 7.5% of jabuticaba pulp spray dried with polydextrose and the control without addition of sucrose. Water holding capacity (WHC), pH, TSS, and aerobic and anaerobic yeast count and LAB of formulations were performed on days 0, 15 and 30 of storage at 4 °C. Samples with sucrose showed higher sensory acceptance, and samples with jabuticaba pulp were characterized as very acid, acid aroma, liquid texture, slightly bitter and slightly sweet. The results of this study showed that the addition of prebiotic jabuticaba pulp is a good strategy to make kefir healthier.